CARBON STORAGE POTENTIAL OF SEAGRASS MEADOWS IN POKEMON BEACH, KARIMUNJAWA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Increased greenhouse gas (GHG) emissions, especially carbon dioxide (CO2), caused global warming. Therefore, mitigation of CO2 emissions is needed by utilizing seagrass potential as carbon storage in biomass. This study aims to determine the carbon storage of above and below ground seagrass in Pokemon Beach in August 2020. The research method used a survey method and descriptive explorative. Samples were taken from 3 stations with line and quadrant transects using the purposive sampling method. Measurement of water quality parameters was performed in-situ. Analysis of seagrass carbon storage was measured using the loss on ignition (LOI) method. The results showed that there are 4 different types of seagrass: Enhalus acoroides, Thalasssia hemprichii, Cymodocea rotundata, and Halophila ovalis, with T. hemprichii dominating. The total density was 295.62 ind/m2, with a 21.29% coverage rate. The overall biomass was 74.42 g/m2, with the above ground biomass of 35.80 g/m2 and the below ground at 38.62 g/m2. Carbon storage amounted to 0.23 tons C/ha, consisting of above ground 0.10 tons C/ha and below ground of 0.13 tons C/ha. The total carbon stock reached 1.13 tons C in the seagrass area of 4903 ha, with an above ground carbon stock of 0.51 tons C and below ground of 0.62 tons C. In general, the below ground seagrass in Pokemon Beach was the largest, storing more carbon.